Autoimmune Encephalitis Due to COVID-19 in a Young Patient - Derakhshani, Forough; Ghazavi, Mohammadreza; Hosseini, Neda (Iranian Journal of Child Neurology, 2023)
Autoimmune encephalitis is an inflammatory condition caused by different factors including viral infections that is diagnosed after ruling out other causes of encephalitis. In the current study, we reported a novel case of autoimmune encephalitis in an 11-year-old girl that presented with seizure, cognitive dysfunction and neurological impairments. During the admission, we observed high levels of anti- N-methyl-D-aspartate receptor (NMDAR) antibody in the cerebrospinal fluid (CSF). She had also positive anti COVID-19 IgG. Therefore, the diagnosis of COVID-19 induced autoimmune encephalitis was certain. The patient received anti-epileptic and anti-viral drugs and also IVIG and rituximab and was discharged with remission. The diagnosis of the case was made by anti-NMDAR antibodies that highlights the importance of this diagnostic tool. Similar cases have been reported earlier but the point of this case was her younger age compared to the previous cases and development of neurological deficit before COVID-19 presentations.